Changes in Saliva Analytes in Dairy Cows during Peripartum: A Pilot Study - Contreras-Aguilar, María D. (Animals (Basel), 2021)
SIMPLE SUMMARY: The use of saliva as a biological fluid to assess welfare and health status is gaining interest nowadays since it can be collected by non-invasive methods without specialized staff. The possibility of measuring analytes in saliva by techniques adapted to automated analyzers is cost-effective, reliable, and replicable. These analytes can provide information useful for the evaluation of welfare and health in dairy cows. In this pilot study, a total of 26 salivary analytes were measured in healthy dairy cows along their peripartum period to assess possible changes and associations with their inflammatory, energy, and milk yield status. Salivary analytes related to stress (cortisol, salivary alpha-amylase, butyrylcholinesterase, and total esterase), immunity (adenosine deaminase), oxidative status (Trolox equivalent antioxidant capacity and the advanced oxidation protein products), and general metabolism (creatine kinase, γ-glutamyl transferase, urea, triglycerides, glucose, and lactate) had significant changes throughout this period. This study indicated that the saliva of dairy cows shows changes in its composition during the transition period and potentially can be a source of biomarkers for monitoring health and welfare. ABSTRACT: This pilot study aimed to study the possible changes in a profile of 26 salivary analytes in thirteen healthy dairy cows along their peripartum period. Analytes associated with the stress (salivary cortisol, salivary alpha-amylase, butyrylcholinesterase, and total esterase), inflammation (adenosine deaminase), oxidative status (total antioxidant capacity and the advanced oxidation protein products), and general metabolism (creatine kinase, γ-glutamyl transferase, urea, triglycerides, glucose, and lactate) varied along the sampling times. A positive correlation between the white blood cells counts, and the lipase, Trolox equivalent antioxidant capacity, advanced oxidation protein products, and lactate levels in saliva were observed at the delivery. A linear association between selected salivary analytes at different sampling times and the milk yield after calving was observed. In conclusion, in our experimental conditions, it was observed that the peripartum period in dairy cows can induce changes in salivary analytes. Some of them were associated with inflammatory status and the capacity of milk production after calving.